Skip to content

Mid

Random Variable

  • The result of experiments (random events)

Markov's Inequality

  • for \(X \ge 0\) and \(a > 0\)
\[ \begin{gather} P(X \ge a) \le \frac{E[X]}{a} \end{gather} \]

Proof

Define a lower bound r.v. \(Y\). That is

\[ Y= \begin{dcases*} a & if $X \ge a$ \\\\ 0 & if $0< X < a$ \end{dcases*} \]

thus,

\[ \begin{gather} Y \le X \end{gather} \]

then,

\[ \begin{gather} E[X]\ge E[Y] = aP(X\ge a) \\\\ \implies P(X\ge a) \le \frac{E[X]}{a} \end{gather} \]

Chebyshev's Inequality

  • for \(X\) is r.v. having mean \(\mu\) and variance \(\sigma^{2}\), then for \(k > 0\),
\[ \begin{gather} P\big(|X-\mu| \ge k\sigma\big) \le \frac{1}{k^{2}} \end{gather} \]

Proof

\[ \begin{gather} P\big(|X-\mu|\ge k\sigma\big)=P\big((X-\mu)^{2}\ge k^{2}\sigma^{2}\big) \end{gather} \]

and by Markov's inequality, we now have,

\[ \begin{gather} P\big(|X-\mu|\ge k\sigma\big)=P\big((X-\mu)^{2}\ge k^{2}\sigma^{2}\big) \le \frac{E\big[(X-\mu)^{2}\big]}{k^{2}\sigma^{2}}=\frac{1}{k^2} \end{gather} \]

Law of Large Number

Weak Law of Large Number

Let \(\bar{X}=\frac{1}{n}\sum\limits{X_i}\), and \(X_i\) are i.i.d., and for any \(\epsilon > 0\)

\[ \begin{gather} P\bigg(|\bar X -\mu| \ge \epsilon\bigg) \to 0, \quad \text{when } n \to \infty \end{gather} \]

Proof

First of all,

\[ \begin{gather} E[\bar X]=\mu \\\\ \text{Var}(\bar X) = \frac{1}{n^{2}}\sum\limits_{i} \text{Var}(X_i) = \frac{\sigma^{2}}{n} \end{gather} \]
  • since i.i.d., \(\text{Cov}(X_i, X_j) = 0\)

then by Chebyshev's inequality,

\[ \begin{gather} P\bigg(|\bar X \ge \mu | \ge k \frac{\sigma}{\sqrt n}\bigg) \le \frac{1}{k^{2}} \\\\ \implies P\bigg(|\bar X \ge \mu | \ge \epsilon \bigg) \le \frac{\sigma^{2}}{n \epsilon ^{2}} \end{gather} \]

Central Limit Theorem

  • The sum of samples is also an normal distribution when \(n\to \infty\).
  • The sample mean is normal distributed.

Let \(X_1, X_2, \dots\) be a sequence of i.i.d. random variables with mean \(\mu\) and variance \(\sigma^{2}\). Then,

\[ \begin{gather} \lim_{n\to \infty} P\left(\frac{\sum\limits{X_i}- n\mu}{\sigma\sqrt{n}} < x\right)=\Phi(x) \end{gather} \]

in which \(\Phi(x)\) is cdf of standard normal distribution.

Monte Carlo Approach

\[ \begin{align} \theta &= \int_0^{1}{g(x)dx} \\\\ &= E\big[g(U)\big] \\\\ &= \lim_{n\to \infty}{\frac{\sum\limits^{n} g(U_i)}{n}} \end{align} \]

Acceptance-Rejection Method

  • required
\[ \begin{gather} \frac{f(y)}{c\,g(y)} \le 1 \end{gather} \]

To solve \(c\), find the maximum of \(\displaystyle {\frac{f(y)}{g(y)}}\). Then find \(y^{*}\) such that

\[ \begin{gather} y^{*} = \arg\max_y \frac{f(y)}{g(y)} \\\\ c \ge \frac{f(y^{*})}{g(y^{*})} \end{gather} \]

Normally, we hope \(c\) as small as possible (to make the rejection rate lower). Thus we could let

\[ \begin{gather} \boxed{ c=\frac{f(y^{*})}{g(y ^{*})} } \end{gather} \]
Standard Normal R.V. Example
  • absolute value of Z
\[ \begin{gather} f(x) = \frac{\mathbf 2}{\sqrt{2\pi}}e^{-x^{2}/2} \qquad 0 < x < \infty \end{gather} \]

and let say \(Y\) be exponential random variable with \(\lambda = 1\)

\[ \begin{gather} g(x) = e^{- x} \end{gather} \]

then,

\[ \begin{gather} \frac{d}{dx}\frac{f(x)}{g(x)} = 0 \\\\ \implies \left(-x+1\right)\exp\left(-\frac{x^{2}}{2}+x\right) = 0 \end{gather} \]

thus

\[ \begin{gather} c =\frac{f(1)}{g(1)} = \frac{\sqrt {2e}}{\sqrt\pi} \end{gather} \]

MM1 queue

First of all, with the entering rate \(\lambda\) and exiting rate \(\mu\), we have the server utilization \(\rho\)

\[ \begin{gather} \rho = \frac{\lambda}{\mu} \end{gather} \]

and the server would be stable iff \(\lambda < \mu\) so that the \(\rho < 1\)

graph LR
s0((0))
s1((1))
s2((2))
sn-1((n-1))
sn((n))
sn+1((n+1))
s0 --"&lambda;"--> s1
s1 --"&lambda;"--> s2
s1 --"&mu;"--> s0
s2 --"&mu;"--> s1

sn-1 --"&lambda;"--> sn
sn --"&lambda;"--> sn+1
sn --"&mu;"--> sn-1
sn+1 --"&mu;"--> sn

The states transition graph have to follow the rule that the outgoing probability must be equal to ingoing probability. Thus it yields the following equations

\[ \left\{ \begin{gather} \lambda p_0 =\mu p_1 \\\\ (\lambda +\mu) p_n = \lambda p_{n-1} + \mu p_{n+1} \end{gather}\right. \]

in which \(n \in ℕ\), and then we can get \(p_2\) as

\[ \begin{gather} (\lambda + \mu) p_1 = \lambda p_0 + \mu p_2 \\\\ \implies \lambda p_1 = \mu p_2 \end{gather} \]

Recursively, we would have

\[ \begin{gather} p_n = \rho \,p_{n-1} \end{gather} \]

and since we known that \(\displaystyle {\sum\limits_i{p_i}=1}\),

\[ \begin{gather} \sum\limits_i{p_i}=p_0\sum\limits_i{\rho^{i}} =p_0\frac{1}{1-\rho} =1 \\\\ \implies p_0 = 1-\rho \\\\ \implies p_n = (1-\rho)\rho^{n} \end{gather} \]

and thus we know that the stable state probability of number of customers \(n\) waiting in queue is a geometric random variable with failure times \(n\).

Number of Customers in System

\[ \begin{align} E[N] &= \sum\limits_n{n\cdot p_n} \\\\ &= (1-\rho)\sum\limits{n\rho^{n}} \\\\ &= (1-\rho)\sum\limits_{i=0}^{\infty}\sum\limits_{j=i}^{\infty}{\rho^{j}} \\\\ &= (1-\rho)\frac{\rho}{(1-\rho)^{2}} \\\\ &\boxed{ = \frac{\rho}{1-\rho} } \end{align} \]

Average Departure Rate

\[ \begin{gather} E[N_D] = \mu\rho = \lambda \end{gather} \]

Waiting Time

  • overall time spent in system \(W\)
\[ \begin{align} E[W] &=\frac{E[N]}{E[N_D]} \\\\ &=\frac{E[N]}{\lambda} \\\\ &=\frac{E[N]/\mu}{\rho} \\\\ &\boxed{ =\frac{1}{\mu(1-\rho)} } \end{align} \]
  • time wait in queue \(W_q\)
\[ \begin{align} E[W_q] &=E[W]-\frac{1}{\mu} \\\\ &=\frac{1}{\mu(1-\rho)}- \frac{(1-\rho)}{\mu(1-\rho)} \\\\ &=\frac{\rho}{\mu(1-\rho)} \end{align} \]

Sample Stats.

Sample Mean

  • denotation
    • \(\theta\) – popluation mean
    • \(\sigma^{2}\) – population variance
    • \(\bar X\) – sample mean
\[ \begin{align} \theta &= E[X_i] \\\\ \sigma^{2} &= \text{Var}(X_i) \\\\ \bar X &\equiv \sum\limits_{i=1}^{n}{\frac{X_i}{n}} \\\\ E[\bar X] &= E \left[\sum\limits_{i=1}^{n}{\frac{X_i}{n}}\right] \\\\ &= \frac{1}{n}E \left[\sum\limits_{i=1}^{n}{X_i}\right] \\\\ &= \frac{1}{n}n\theta = \theta \end{align} \]
\[ \begin{align} E\left[\left(\bar X - \theta\right)^{2}\right] &= \text{Var}(\bar X) \\\\ &= \text{Var}\left(\sum\limits_{i=1}^{n}{\frac{X_i}{n}}\right) \\\\ &= \frac{1}{n^{2}}\text{Var}\left(\sum\limits_{i=1}^{n}{X_i}\right) \\\\ &= \frac{1}{n^{2}}n\sigma^{2} =\frac{\sigma^{2}}{n} \end{align} \]

Binomial and Negative Binomial

Binomial Distribution

  • distribution of number of success \(r\) given number of trails \(n\)
\[ \begin{gather} P(X=r)=\binom{n}{r}p^{r}(1-p)^{n-r} \end{gather} \]

Negative Binomial Distribution

  • distribution of number of trails \(n\) given number of success \(r\)
    • namely, distribution of number of failures \(k\) given number of success \(r\)
\[ \begin{gather} P(X=n)=\binom{n-1}{r-1}p^{r}(1-p)^{n-r} \end{gather} \]

Geometric Distribution

  • number of trails \(n\) until success
\[ \begin{gather} P(X=n)=p(1-p)^{n-1} \end{gather} \]

Generation Method

  • CMF
\[ \begin{gather} F(i) = \sum\limits_{n=1}^{i}{p\,q^{n-1}}=p\,\frac{1-q^{i-1}}{1-q}=1-q^{i-1} \end{gather} \]

let

\[ \begin{gather} U=G(i) = 1-F(i) = q^{i-1} \end{gather} \]

thus

\[ \begin{gather} i-1 = \log_qU \\\\ \implies G^{-1}(U) = \lfloor {\log_{q}{U}} \rfloor + 1 \end{gather} \]

Poisson Distribution

  • \(\text{Pois}(\lambda)\)
  • Considering events occur with rate \(r\), with time interval \(t\), there would be average number of events \(rt\) per interval.
    • say that \(\lambda = rt\), expected rate of occurrences
    • Split the time interval \(t\) in to \(N\) pieces and make the sub-interval \(t'\) very small(i.e. \(N\) very large).
    • \(t' = t/N \text{ where } N \to \infty\quad \text{then } \quad r\,t' \ll 1\)
    • if \(rt' \ll 1\), it approximates to do one Bernoulli trails in each time interval \(t'\).
    • \(\text{Pois}(\lambda) \equiv B(n=N,\, p=rt'=\lambda/N)\equiv B(n \to \infty, p \to 0)\)
  • \(E_{X\sim Pois}\big[X\big] = \lambda = np = rt\)
  • \(X \sim \text{Pois}(\lambda )\), indicates \(X\) is the number of events occurs in unit time interval (and the event rate is \(\lambda\)).
\[ \begin{align} P\{X=i\} &= \binom{n}{i}p^{i}\,(1-p)^{n-i} \\\\ &= \binom{\cancel{n}}{i} \frac{\lambda ^{i}}{\cancel {n^{i}}}\,(1-p)^{n-i} \\\\ &= \frac{\lambda^{i}}{i!}(1-p)^{n-i} \\\\ &= \frac{\lambda^{i}}{i!}(e^{-p})^{n} \\\\ &= \frac{\lambda^{i}}{i!}e^{-\lambda} \end{align} \]

hint

\[ \begin{align} \lim_{x\to0}e^{x}=e^{0}\left(1+\frac{x}{1!}+\frac{x^{2}}{2!}\right)\approx1+x \end{align} \]

Generation Method

  1. Generate several exponential random variable \(E_i \sim \text{Exp}(\lambda )\)
  2. until \(E_1 +E_2 + \cdots + E_i \ge 1 >E_1 + E_2 + \cdots + E_{i-1}\)

Exponential Distribution

  • time between events in Poisson process
  • continuous analogue of the geometric distribution.

  • CDF

    • take \(Y \sim \text{Pois}(\lambda )\)
    • split unit time interval to \(1/N\), where \(N\) is large
    • then \(p=\lambda /N\)
\[ \begin{gather} P(X \ge k) = (1-p)^{kN} = e^{-kNp} = e^{-\lambda k} \\\\ F(x) = 1-P(X\ge x) = 1- e^{-\lambda x} \end{gather} \]
  • PDF
\[ \begin{gather} f(x) = F'(x) = e^{-\lambda x} \end{gather} \]

Generation Method

Since,

\[ \begin{gather} F(x) = 1 - e^{-\lambda x } \\\\ \implies F^{-1}(U) = \frac{\ln (1-U)}{-\lambda} \end{gather} \]

identically,

\[ \begin{gather} F^{-1}(U) = F^{-1}(1-U) = -\frac{1}{\lambda}\ln U \end{gather} \]